1966
DOI: 10.1246/bcsj.39.2467
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogenation and Hydrogenolysis. IX. The Hydrogenation of Benzyl Alcohol with Platinum Metal Catalysts

Abstract: The rate of the hydrogenation of benzyl alcohol with a rhodium catalyst decreases markedly in the course of the reaction, accompanied by the formation of an increasing amount of cyclohexanecarboxaldehyde with the conversion of the alcohol. The decrease in the rate is only slight with a platinum catalyst, however, and the formation of the aldehyde is much less than with the rhodium catalyst. It has been shown that cyclohexanecarboxaldehyde is an effective catalyst poison in the hydrogenation of benzyl alcohol, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1967
1967
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…In route 1, four hydrogen atoms are introduced into benzyl alcohol, giving rise to 1-cyclohexenylmethanol. The resulting 1-cyclohexenylmethanol is then converted to cyclohexanecarbaldehyde …”
Section: Discussionmentioning
confidence: 99%
“…In route 1, four hydrogen atoms are introduced into benzyl alcohol, giving rise to 1-cyclohexenylmethanol. The resulting 1-cyclohexenylmethanol is then converted to cyclohexanecarbaldehyde …”
Section: Discussionmentioning
confidence: 99%
“…It can be seen that in entry 1 in Table 1, the selectivity of cyclohexanemethanol was 94.8% at 323 K, which was significantly higher than several reported values in the previous studies. 2,3,10 This phenomenon may be explained by the less favored C-O bond cleavage, also known as hydrogenolysis, during mild temperature condition. Therefore, instead of mainly producing toluene and methylcyclohexane at high temperatures, the desired product cyclohexanemethanol could be obtained in high selectivity at mild temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Nishimura and Hama reported the main hydrogenation products of benzyl alcohol. 3 Their research showed that Rh catalysts could have been poisoned due to the formation of the byproduct, cyclohexanecarboxaldehyde. However, this product was not observed when using Pt catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Significant decarbonylation of benzaldehyde occurred, in addition to evidence of ring hydrogenation depending on the reaction conditions. 61,77 Nishimura et al used Pt and Pt-Rh catalysts in the condensed-phase hydrogenolysis and hydrogenation of benzyl alcohol at 25°C…”
Section: Benzyl Alcoholmentioning
confidence: 99%
“…with some additives such as acetic acid. 77 Hydrogenation of the aromatic ring followed by hydrogenolysis was the primary pathway in which several cyclohexane derivatives were formed.…”
Section: Benzyl Alcoholmentioning
confidence: 99%